2007
DOI: 10.1002/jcc.20885
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental vibrational frequencies and dominant resonances in methylamine isotopologues by ab initio and density functional theory methods

Abstract: Ab initio and density functional theory (DFT) calculations were performed for obtaining fundamental vibrational frequencies of methylamine, CH3NH2, and its deuterated variants CH3ND2, CD3NH2, and CD3ND2. The calculations were carried out using the CCSD(T) coupled cluster approximation with cc-pVTZ and cc-pVQZ basis sets, and by the DFT method with the semiempirical hybrid functional B97-1 with polarization consistent pc-2 and pc-3 basis sets. Reasonable performance of the DFT harmonic and ab initio harmonic ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…106.8 A (1,3,8) (1,4,11) 113.3 A (1,3,9) (1,4,13) 109.8 A (1,3,10) (1,4,12) 110.1 A (9,3,10) (12,4,13) 107.7 A (11,4,13) (8,3,9) 108.0 A (11,4,12) (8,3,10) 107.8…”
Section: Supplementary Informationmentioning
confidence: 99%
See 2 more Smart Citations
“…106.8 A (1,3,8) (1,4,11) 113.3 A (1,3,9) (1,4,13) 109.8 A (1,3,10) (1,4,12) 110.1 A (9,3,10) (12,4,13) 107.7 A (11,4,13) (8,3,9) 108.0 A (11,4,12) (8,3,10) 107.8…”
Section: Supplementary Informationmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Methylamine is considered a small molecule from the theoretical point of view, therefore it is appropriate to be studied using high level theoretical quantum chemical methodologies, having received many contributions. [7][8][9][10][11][12][13][14] Lee et al 8 investigated the origin of the structural stability of methylamine concluding that the stereo electronic effect is the major interaction force affecting its stability. Csonka and Sztraka 9 using density functional and post-HartreeFock methodologies showed that the density functional BP86/6-311G(d) method provides reliable results for geometry and vibrational frequencies, as compared with the experimental results.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…29 However, in the C−H stretching region we instead compare our measured values to full anharmonic ab initio calculations of the Fermi resonances. 33 Inspection of Figure 1 shows the v 8 and v 9 absorptions both show additional fine structure not observed for the other vibrational modes. The v 8 peak shows fine structure with three resolved peaks at 1043.9, 1044.2, and 1044.5 cm −1 in the as-deposited sample and the v 9 peak shows evidence for four resolved peaks at 786.8, 789.6, 790.6, and 791.9 cm −1 .…”
Section: Experimental Results and Analysismentioning
confidence: 90%
“…In the absence of Fermi resonances we should only observe three peaks (ν 3 , ν 2 and ν 11 absorptions) in this region. However, instead we observe multiple peaks, which we can assign on the basis of the anharmonic calculations of Levi et al 33 For example, the intensity of the 2v 6 overtone and the v 5 + v 6 combination band, which are generally expected to be much weaker than any of the fundamental vibrational absorptions, are greatly amplified in this region. This amplification results from intensity "borrowing" of the weak overtone (dark) transition from the fundamental (bright) transition by mixing in fundamental character to the overtone transition.…”
Section: Experimental Results and Analysismentioning
confidence: 92%